Effect of a Nutrition Diet on Health Status of Physically Challenged Students at Ade Okubanjo Institute for the Blind, Ijebu-Igbo - Titilayo Monsurat Musa; Adekola Ridwan Ademola; Adeleye Oluwagbemiga Adewale; Khadijat Oluwapelumi Popoola (Journal of Social Behavior and Community Health)
Background: The role of balanced diet in the life of an individual physically challenged or not cannot be overlooked. The condition of the physically challenged children attracts little or no attention. Several factors have been identified as causes of malnutrition in physically challenged persons. A nutritional diet is one of the factors that can help to reduce this phenomenon. The study was designed to examine the effect of a nutrition diet on health status of physically challenged students at Ade Okubanjo Institute for the Blind at Ijebu-Igbo. Method: This study used a descriptive survey research design and was conducted in 2022. 120 students were selected as the population of this study of which 100 were retuned valid. The research location was Ade Okubanjo Institute for the Blind, Ijebu-Igbo. A self-structured questionnaire was used to measure the nutrition diet of physically challenged students. To do so, 100 questionnaires were analyzed using a purposive sampling techniques method.  Nutritional diet and health status questionnaire was the instrument used for this study and questions about physical performance, nutritional diet, lack of adequate nutrition and family/parental status questions were asked from the participants. Cronbach’s alpha of NHSQ was 0.72. The data analysis method included the descriptive statistics were analyzed using chi-square. Result: Findings revealed that physical activities performance will significantly influence the nutrition diet of physically challenged children (Cal. value = 125.748a,, p-value = .000.), Lack of adequate nutrition will significantly influence the nutrition diet of physically challenged children (Cal. value = 46.180a,, p-value = .000.) also mental health status significantly influence the nutrition diet of physically challenged children (Cal. value = 41.165a,, p-value = .000.), Family/parental status will significantly affect the nutritional diet intake of the physically challenged (Cal value = 41.165a, , p-value = .000.). Conclusion: The findings concluded that Physical performance, Lack of adequate nutrition, Mental status and Family/parental status significantly affect the nutritional diet intake of the physically challenged students at Ade Okubanjo Institute for the Blind.